THE IMPORTANCE OF TEACHING ENGLISH IN SCHOOLS AND UNIVERSITIE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
English is a global language used for communication, business, science, technology, and entertainment. As such, teaching English in schools has become essential for students to develop the necessary language skills to communicate, learn, and succeed academically and professionally. This article explores the importance of teaching English in schools and its various benefits for students. Drawing on a literature analysis and research methodology, the article highlights the benefits of English language education in promoting global communication, increasing employability, facilitating access to information, promoting cultural exchange, and preparing students for higher education opportunities. However, the article also acknowledges the challenges of teaching English in schools, such as the lack of qualified teachers, inadequate resources, and cultural barriers, and emphasizes the need to prioritize and invest in English language education to prepare students for the challenges and opportunities of a globalized world.